Using focus groups to inform a brief video intervention to reduce public stigma toward Black youth living with psychosis - Jankowski, Samantha E.; Pope, Leah G.; Smith, Stephen; Pagdon, Shannon; Dixon, Lisa B.; Amsalem, Doron (Frontiers in Psychiatry, 2023)
Objective Black individuals living with psychosis are at risk for stigma and marginalization due to systematic discrimination and barriers to receiving treatment. Social contact-based interventions have the potential to reduce stigma; however, interventions with elements specific to the experiences of Black youth are limited. Therefore, we aimed to gather input from Black youth living with psychosis to develop a social contact-based, brief video intervention to reduce public stigma toward Black youth with psychosis. Methods Two 90-min focus groups were conducted with seven young Black individuals ages 18–30 with First Episode Psychosis from OnTrackNY. Participants were asked about their experiences of stigma and racial discrimination, and their perspectives on a video intervention. Focus group transcripts were analyzed using thematic content analysis. Results Themes that emerged included: the salience of stigma and racial experiences for some participants and not others; the linking of religiosity and symptoms in Black communities; the importance of taking responsibility for recovery as a coping strategy to counteract stigma; and mixed views on creating a video intervention specific to Black youth. Conclusion Meaningful and empowering involvement of individuals with lived experience of psychosis is essential to create stigma reducing interventions. Input from Black youth living with psychosis assisted in developing a culturally tailored brief video-based intervention to reduce public stigma toward Black youth with psychosis that included information about the protagonist’s experience of race and mental illness, specifically family, religious, and community-based experiences.